FORMALIN CONTENT OF PROCESSED FISH PRODUCTS IN JAMBI TRADITIONAL MARKETS USING TEST KIT - Hasanah, Hasanah; Wulandari, Wulandari; Afriani, Afriani; Hariski, M.; Arbajayanti, Rahma Dini (Jurnal Perikanan Unram, 2025)
Fish is a fishery product that has high nutritional value. Fish can be processed into various processed products. Processed fish products generally have the characteristic of not lasting long when stored at room temperature so that in the food processing, additives are added. Hazardous food additives that are often used in processed fish products are formalin. Formalin is a preservative that can cross-link with protein so as to prevent damage to product and can extend its shelf life. This study aims to determine the formalin content in processed fish products, namely fish meatballs and salted fish in traditional markets in Jambi City. The research method used laboratory experiments with 4 treatments and 3 replications. The results showed that the samples of fish meatballs and salted fish as a whole were positive for formalin. This shows that the food safety of processed products in traditional markets in Jambi is still low. The knowledge and awareness of the fisheries processing community about hazardous food additives is still low.